PERANGKAT LUNAK UNTUK PENGUJIAN DENGAN BALANCE SYSTEM DI TEROWONGAN ANGIN - Hastono, Prih
Abstrak : It has been done in the thesis a development of ADAS software used to support the functionality of data acquisition system for aerodynamic load measurement in the low speed wind tunnel testing using balance system. The software has several capabilities, including the capability to perform acquiring tunnel references data, acquiring aerodynamic load data on the model of an aircraft or its component includes drag, lift, side force, pitch moment, yaw moment and roll moment using external balance, and capability to control the balance system angle representing angle of attact in the half model testing and side slip angle in the full model testing. The equation for the balance system measurement is approached by a second order matrix equation. The development conducted follows the standard for software development DoD-STD-2167A trough RDL Life Cycle referenced from the Thomson-CSF Methodological Baseline. The development process is started from requirement analysis using functional approach by means of SART method. The TOOD method is used for object design and analysis, which determines the objects by translation from SART model and the real world object in the case. Implementation process for the design is conducted by means of Borland C++ Builder version 3.0 language for Microsoft Window 95 operating system. Verification processes for the development are review, analysis and testing. Unitary and integration testing performed by Black Box method notifies the result that the software meets its requirements. Validation testing conducted trough comparison between the software behavior found during execution and the specified behavior establishes that the ADAS software is valid.